189k views
3 votes
Which function is equivalent to h(x)=10x^(2+9x-1)

User BenV
by
5.1k points

2 Answers

3 votes

Answer: h(x) = (x+1) (10x-1)

Step-by-step explanation: I got it correct

User Mehul Bisht
by
4.9k points
4 votes

Answer:

h(x) = (10x - 1)(x + 1)

Explanation:

Given

h(x) = 10x²+9x-1

Required

Get its equivalent

To do this, we simply factorize h(x)

We have that:

h(x) = 10x²+9x-1

Expand

h(x) = 10x² + 10x - x - 1

Factorize

h(x) = 10x(x + 1) -1(x + 1)

This gives:

h(x) = (10x - 1)(x + 1)

Hence, the equivalent of h(x) = 10x²+9x-1 is h(x) = (10x - 1)(x + 1)

User Caspar Geerlings
by
4.8k points